Divisive Politics and Accountability - Áron Kiss (Hungarian Academy of Sciences, Institute of Economics, 2011)
The paper analyzes a political accountability game with an electorate of 'partisan' and 'independent' voters. It is shown that politicians have a strategic incentive to engage in 'divisive politics', that is, to force some independent voters to take sides, even if the direct electoral benefits are higher for their opponents than for themselves. By polarizing the electorate, the incumbent politician weakens the ability of independent voters to make him accountable for his policies in the common interest. Moreover, the interests of the incumbent and the opposition are aligned: the opposition also benefits from divisive politics because, in equilibrium, its election probability increases.
Keywords: D72; 330; political accountability; political agency; divisive politics; democracy in divided societies; Politische Entscheidung; Wahlverhalten; Spieltheorie